From Sentiment to Science — docomomo comes of Age - Allan, John (Docomomo Journal, 2013)
The following keynote lecture was presented at the 12th International docomomo Conference that took place in Espoo, Finland, in August 2012. The author, an active member of docomomo since its creation, used this opportunity to do what is traditional when someone ‘comes of age’, that is, use it as a milestone to look back at where docomomo came from, and forward to what it might become.